2019
DOI: 10.1002/elan.201900057
|View full text |Cite
|
Sign up to set email alerts
|

Redox Denaturation of Proteins: Electrochemical Treatment of Egg Plasma

Abstract: Although acid/base reactions are used widely to denature proteins during food processing, the application of reduction/oxidation (redox) reactions are relatively rare in this field. Herein, we demonstrate a “redox denaturation” of proteins, using egg plasma as a model. Electrochemical treatment of egg plasma in the presence of iodide ion (I−) selectively induced intramolecular disulfide bond formations, resulting in a different type of denaturation than that achieved via heat treatment. The reaction mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Neither protein aggregation nor RBC clots formed by the use of low-temperature plasma have been reported except in our experimental results [27][28][29]. However, it has recently been reported that the formation of disulfide bonds in food proteins was achieved by an electrochemical reaction in solution [35][36][37]. Studies on protein reactions using electric, photonics, or magnetic fields have also become popular in the field of organic chemistry.…”
Section: Hemolytic Coagulation Of Rbc Serum Protein Aggregation Plate...mentioning
confidence: 66%
“…Neither protein aggregation nor RBC clots formed by the use of low-temperature plasma have been reported except in our experimental results [27][28][29]. However, it has recently been reported that the formation of disulfide bonds in food proteins was achieved by an electrochemical reaction in solution [35][36][37]. Studies on protein reactions using electric, photonics, or magnetic fields have also become popular in the field of organic chemistry.…”
Section: Hemolytic Coagulation Of Rbc Serum Protein Aggregation Plate...mentioning
confidence: 66%
“…Noticed that, it is universally known that proteins can interfere electrochemical reaction. For example, proteins adsorbing on the electrode surface may raise impedance, [24] and the redox properties of proteins [25] will also influence electrochemical products. Thus, it is essential to explore whether the existence of proteins will disturb the ECL reactions on electrodes.…”
Section: Resultsmentioning
confidence: 99%